Front Cover: Bithiazole Inhibitors of Phosphatidylinositol 4‐Kinase (PI4KIIIβ) as Broad‐Spectrum Antivirals Blocking the Replication of SARS‐CoV‐2, Zika Virus, and Human Rhinoviruses (ChemMedChem 23/2021). (6th December 2021) - Grazia Martina, Maria; Vicenti, Ilaria; Bauer, Lisa; Crespan, Emmanuele; Rango, Enrico; Boccuto, Adele; Olivieri, Noemi; Incerti, Matteo; Zwaagstra, Marleen; Allodi, Marika; Bertoni, Simona; Dreassi, Elena; et al.
Abstract : The Front Cover shows bithiazole derivatives acting as broad‐spectrum antiviral agents (BSAAs) by targeting human host cells. These molecules block the replication of human rhinoviruses (hRVs) and Zika virus (ZIKV) via inhibition of the intracellular protein PI4KIIIβ while the inhibition of SARS‐CoV‐2 entry and replication seems to be connected with the modulation of an additional target. Cover design by Marco Radi. More information can be found in the Communication by Maria Grazia Martina, Marco Radi et al .